‘Hard’ and ‘soft’ approaches in active transport promotion: analysis and mapping of government policies - Nicholas J. R. Hunter; Benjamin Cramer; Erica Randle; Katherine A. Hunter (Urban, Planning and Transport Research)
Active transport can be promoted through approaches ranging from environmental changes (e.g. bike lanes or paths) to social programs (e.g. training and education). This study reviewed how local and state governments in Victoria, Australia – a region with low active transport participation – prioritise these different approaches. Using a PRISMA scoping review methodology, we identified 996 active transport policies within 123 strategic documents across transport, sustainability, and health sectors. Our findings suggest that governments in Victoria take a multifaceted approach to active transport promotion, comprising policies that achieve one of the three functions: (i) modifying the built environment (‘hard measures’; 45.1% of policies analysed); (ii) changing social attitudes, motivations and capabilities (‘soft measures’; 27.8%); and (iii) planning and decision-making within government to support active transport promotion (‘governance measures’; 24.6%). These three measures correspond to different policy categories in the behaviour change wheel framework, suggesting that each measure has specific functions for targeting active transport behaviours. This mix of ‘hard’ and ‘soft’ approaches to active transport promotion was observed in local government policies across both metropolitan and regional areas of Victoria. Applying these methods to other areas will help determine the most effective combination of approaches for maximising active transport uptake.